IMPLEMENTASI KEBIJAKAN PEMERINTAH NOMOR 198 TAHUN 2022 TENTANG PEMBENTUKAN KELOMPOK SADAR WISATA OLEH DISPARBUDPORA KABUPATEN SUMEDANG - Tita Latipah (LPPM UNSAP, 2026)
This study aims to examine the implementation of Government Policy Number 198 of 2022 concerning the establishment of Tourism Awareness Groups (Pokdarwis) by the Department of Tourism, Culture, Youth, and Sports of Sumedang Regency. The background of this research lies in the lack of socialization conducted by the Tourism Division, the limited resources available, and the suboptimal bureaucratic workflow within the department. This research employs a qualitative method with purposive sampling involving four informants from within the Tourism Department. Data collection techniques include field studies and literature studies through observation, interviews, documentation, and triangulation. Data analysis techniques consist of data collection, data reduction, data display, and conclusion drawing and verification. The results show that the policy implementation has been fairly well-executed, particularly in terms of communication and the positive attitude of implementers. However, challenges remain in terms of human resources, facilities, and budget constraints. The bureaucratic structure already has clear SOPs. The main obstacles include insufficient socialization, uneven dissemination of information, varying levels of community support, and imbalanced task distribution due to limited personnel. Efforts made include strengthening internal coordination, technical training, SOP development, cross-sector collaboration, and a proactive village outreach approach.